Plant Diversity and Potentials in Campus UIN Walisongo Semarang - Niken Kusumarini; Baiq Farhatul Wahidah; Arifin Surya Dwipa Irsyam (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
Various plants were planted as shade trees and ornamentals in campus of UIN Walisongo Semarang. Many plants were also growing wild in this area. Plant dentification is an important step so that people know about plant diversity and plant potentials. Therefore, this research aimed to provide information on the diversity of plants and their potentials in UIN Walisongo Semarang. Research was conducted by using survey method, identification, documentation, species validation and literature review. Field observations were conducted in Campus I, II and III in Ngaliyan Semarang. This research obtained approximately 231 species, which were classified based on wild or cultivated, their habits, and their potentials description. Many plants also used as teaching material in botanic course.